A legacy of passion and dedication: new taxa and notes on Cerambycidae (Coleoptera) from the late James Cope collection - Santos-Silva, Antonio; Bezark, Larry G.; Nascimento, Francisco Eriberto De Lima (Zootaxa, 2025)
The material examined in this work belongs to the collection of James S. Cope (1941-2024). His collection of over 10,000 specimens of Cerambycidae is currently housed in the California State Collection of Arthropods at the California Department of Food & Agriculture Sacramento, California, USA. Two new species are described: Odontogracilis copei sp. nov. (Cerambycinae, Rhinotragini) from Mexico: and Sternacutus monnei sp. nov. (Lamiinae, Acanthocinini) from Panama. Euderces reichei LeConte, 1873 is redescribed based on an entirely dark specimen from Mexico. Lithargyrus Martins & Monné, 1979 (Lamiinae, Acanthocinini) is recorded from Mexico for the first time; the possible synonymy between L. guadeloupensis (Villiers, 1980) and L. melzeri Martins & Monné, 1979 is discussed. The female of Alphinellus minutus Bates, 1881 (Lamiinae, Desmiphorini) is described for the first time.